2015
DOI: 10.1111/nmo.12519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fat and food consistency on gastroparesis symptoms in patients with gastroparesis

Abstract: A high-fat solid meal significantly increased overall symptoms among individuals with gastroparesis, whereas a low-fat liquid meal had the least effect. With respect to nausea, low-fat meals were better tolerated than high-fat meals, and liquid meals were better tolerated than solid meals. These data provide support for recommendations that low-fat and increased liquid content meals are best tolerated in patients with symptomatic gastroparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 31 publications
(31 reference statements)
0
32
0
3
Order By: Relevance
“…A recent study conducted by Ali Abdelhamid et al 16 indicated that lipid absorption in the small intestine was decreased in critically ill patients compared with healthy volunteers by measuring exhaled 13 CO 2 and serum 3‐OMG concentrations. Another study conducted by Homko et al 19 also demonstrated that a high‐fat diet significantly increased the overall symptoms among patients with gastroparesis, whereas a low‐fat diet resulted in the least symptoms. Therefore, one of the possible mechanisms for the high incidence of feeding intolerance was that fat emptying and absorption were severely damaged, perhaps causing poor GI motility and damaged food digestion and absorption in critically ill patients.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study conducted by Ali Abdelhamid et al 16 indicated that lipid absorption in the small intestine was decreased in critically ill patients compared with healthy volunteers by measuring exhaled 13 CO 2 and serum 3‐OMG concentrations. Another study conducted by Homko et al 19 also demonstrated that a high‐fat diet significantly increased the overall symptoms among patients with gastroparesis, whereas a low‐fat diet resulted in the least symptoms. Therefore, one of the possible mechanisms for the high incidence of feeding intolerance was that fat emptying and absorption were severely damaged, perhaps causing poor GI motility and damaged food digestion and absorption in critically ill patients.…”
Section: Discussionmentioning
confidence: 89%
“…Nausea was highest with the high-fat solid meal and lowest with the low-fat liquid meal. This provides support for recommending low-fat and more liquid meals in gastroparesis to reduce symptoms, but longer term diet studies are needed [26].…”
Section: Dietary Interventionsmentioning
confidence: 88%
“…The severity of eight symptoms was rated on a 0-4 scale every 15 min, before and up to 4 h after meal ingestion [26]. Both high-fat meals as well as low-fat solid meal were associated with higher symptom burden.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…29 A high-fat solid meal significantly increased overall symptoms among individuals with gastroparesis. 30 On the other hand, saltine crackers, jello, and graham crackers moderately improved symptoms, and 12 additional foods were tolerated without provoking symptoms. These were: ginger ale, gluten-free foods, tea, sweet potatoes, pretzels, white fish, clear soup, salmon, potatoes, white rice, popsicles, and applesauce.…”
Section: Advances In Dietary Recommendationsmentioning
confidence: 98%